Reconceptualizing Aesthetic Cosmopolitanism: Evidence From the Early Consecration of Anglo-American Pop-Rock in Italy. (January 2021) - Varriale, Simone
This article explores how foreign, recently imported cultural forms can redefine the dynamics of legitimation in national cultural fields. Drawing on archival research, the article discusses the early consecration of Anglo-American pop-rock in 1970s Italy and analyzes the articles published by three specialist music magazines. Findings reveal the emergence of a shared pop-rock canon among Italian critics, but also that this "cosmopolitan capital" was mobilized to implement competing editorial projects. Italian critics promoted both different strategies of legitimation vis-à-vis contemporary popular music and opposite views of cultural globalization as a social process. Theoretically, the article conceptualizes "aesthetic cosmopolitanism" as a symbolic resource that can be realized through competing institutional projects, rather than as a homogeneous cultural disposition.